'Indirect' challenges from science to clinical practice. Issue 1 (1st January 2016) - Anderson, Sandra D.
Abstract : Indirect challenges act to provoke bronchoconstriction by causing the release of endogenous mediators and are used to identify airway hyper-responsiveness. This paper reviews the historical development of challenges, with exercise, eucapnic voluntary hyperpnoea (EVH) of dry air, wet hypertonic saline, and with dry powder mannitol, that preceded their use in clinical practice. The first challenge developed for clinical use was exercise. Physicians were keen for a standardized test to identify exercise-induced asthma (EIA) and to assess the effect of drugs such as disodium cromoglycate. EVH with dry air became a surrogate for exercise to increase ventilation to very high levels. A simple test was developed with EVH and used to identify EIA in defence force recruits and later in elite athletes. The research findings with different conditions of inspired air led to the conclusion that loss of water by evaporation from the airway surface was the stimulus to EIA. The proposal that water loss caused a transient increase in osmolarity led to the development of the hypertonic saline challenge. The wet aerosol challenge with 4.5% saline, provided a known osmotic stimulus, to which most asthmatics were sensitive. To simplify the osmotic challenge, a dry powder of mannitol was specially prepared and encapsulated. The test pack with different doses and an inhaler provided a common operating procedure that could be used at the point of care. All these challenge tests have a high specificity to identify currently active asthma. All have been used to assess the benefit of treatment with inhaled corticosteroids. Over the 50 years, the methods for testing became safer, less complex, and less expensive and all used forced expiratory volume in 1 sec to measure the response. Thus, they became practical to use routinely and were recommended in guidelines for use in clinical practice.